Challenges And Goals For Accelerators In The XXI Century - Myers, Stephen; Bruning, Oliver (World Scientific Publishing Company, 2016)
The past 100 years of accelerator-based research have led the field from first insights into the structure of atoms to the development and confirmation of the Standard Model of physics. Accelerators have been a key tool in developing our understanding of the elementary particles and the forces that govern their interactions. This book describes the past 100 years of accelerator development with a special focus on the technological advancements in the field, the connection of the various accelerator projects to key developments and discoveries in the Standard Model, how accelerator technologies open the door to other applications in medicine and industry, and finally presents an outlook of future accelerator projects for the coming decades.